Evaluating the Impact of Prevention and Early Intervention Activities on the Mental Health of California's Population - Watkins, Katherine E. (RAND Corporation, 2012)
This report describes development of a statewide framework for evaluating and monitoring the short- and long-term impact of prevention and early intervention funding for mental health services on the California population. It details the approach, the data sources, and the frameworks developed: an overall approach framework and outcome-specific frameworks.